STRATEGI PENGEMBANGAN KOMPETENSI KARYAWAN DALAM MENGHADAPI TRANSFORMASI DIGITAL: STUDI KUALITATIF BERBASIS LITERATUR - Hendrick Sasimtan Putra; Marto Silalahi; Sudung Simatupang; Debi Eka Putri (Universitas Dharmawangsa, 2026)
The rapid and continuous advancement of digital technologies has significantly reshaped organizational practices, extending beyond operational processes to include communication patterns, decision-making mechanisms, and value creation. In this context, human resource readiness becomes a critical determinant of organizational success, positioning employee competency development as a strategic priority. This study aims to explore and synthesize various strategies that organizations can adopt to enhance employee competencies in the era of digital transformation. A qualitative approach was employed using a literature review design, drawing upon relevant academic sources such as peer-reviewed journal articles, scholarly books, and prior empirical studies. The analysis was conducted systematically through identification, categorization, and synthesis to generate comprehensive insights.The findings reveal that employee competency development plays a pivotal role in strengthening organizational readiness in response to technological disruption. Effective strategies include the adoption of digital-based learning systems, the implementation of continuous skill development initiatives (reskilling and upskilling), and the cultivation of an organizational culture that fosters learning and innovation. These strategies contribute not only to improving employees’ digital capabilities but also to enhancing organizational sustainability and competitiveness in an increasingly dynamic environment.